Strategi Menjadikan Indonesia Sebagai Negara Pengekspor Utama Dunia - Andika Yuda Prasetya; Nurul Azizah (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Indonesia, a country rich in natural resources, has the potential to become one of the world's major exporters. Indonesia is required to compete in various international businesses due to its wealth of natural resources and a sizable domestic market. This article looks at the key elements that can turn Indonesia into a major exporter, such as improving infrastructure, developing human capital, and implementing policies to encourage trade and investment. By enhancing these elements, Indonesia can attract more foreign capital, expand its export potential, and provide more jobs for its citizens. This article also reviews the obstacles faced by Indonesia in achieving its goals, such as ineffective administration, lax regulations, and low productivity. However, with the right strategy and commitment, Indonesia can become a major world exporter and contribute to the country's economic growth and development.